Right ventricular myocardial infarction: echocardiographic evidence among patients with inferior wall myocardial infarction (Faculty of Medicine Universitas Indonesia, 2006)
Right ventricular myocardial infarction (RVMI) predominantly a complication of inferior wall myocardial infarction is a distinct clinical entity in which major hemodynamic disturbance may occur. Bedside hemodynamic measurement, electrocardiography, gated blood pool radionuclide angiography and echocardiography are used to identify right ventricular involvement in setting of inferior wall infarction. RVMI as assessed by various diagnostic methods accompanies 30 to 50% of inferior wall infarction. We studied 37 consecutive patients of acute inferior wall infarction (by non invasive method) to determine echocardiographic evidence of RVMI and compared its sensitivity to electrocardiography and clinical criteria. On echocardiography 12 out of 37 patients (32%) had right ventricular involvement. Kussmaul's signs was present in 27% of the patients and it had sensitivity of 50%, specificity of 88% and predictive accuracy of 70%. Right sided precordial leads (V3R â V4R) on electrocardiography showed evidence of RVMI in 30% of patients with sensitivity, specificity and predictive accuracy of 67%, 88% and 73% respectively. Echocardiographic features included enlargement of right ventricle and hypokinesia or akinesia of right ventricular wall. Right ventricular dilatation and dysfunction is gained from relative right and left ventricular dimension on echocardiography. It is more sensitive and specific than clinical signs and ECG. (Med J Indones 2006; 15:94-9)